2011
DOI: 10.1002/cncr.26599
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of doxorubicin and weekly paclitaxel efficacy in metastatic angiosarcomas

Abstract: BACKGROUND: Data regarding the role of anthracyclines and taxanes as first-line treatments of metastatic angiosarcoma are limited. METHODS: Records of 117 metastatic angiosarcoma patients who were treated with either doxorubicin or weekly paclitaxel were reviewed. RESULTS: Seventy-five patients (64%) were treated with weekly paclitaxel and 42 (36%) with single-agent doxorubicin. Patients in the weekly paclitaxel group were older and more frequently had angiosarcomas arising from the skin. In the doxorubicin gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 39 publications
11
95
2
Order By: Relevance
“…This finding could either reflect the negative impact of microscopic residual disease, or the propensity of more extensive (and thus prognostically poorer tumours) to be unamenable to complete surgical extirpation. Palliative chemotherapy with either doxorubicin or paclitaxel has been reported to confer superior outcomes for metastatic AS in previously reported series [29,31]; we were unable to discern such an effect in our series.…”
Section: Discussioncontrasting
confidence: 53%
“…This finding could either reflect the negative impact of microscopic residual disease, or the propensity of more extensive (and thus prognostically poorer tumours) to be unamenable to complete surgical extirpation. Palliative chemotherapy with either doxorubicin or paclitaxel has been reported to confer superior outcomes for metastatic AS in previously reported series [29,31]; we were unable to discern such an effect in our series.…”
Section: Discussioncontrasting
confidence: 53%
“…Some clinical studies of angiosarcoma have recently shown that single-agent doxorubicin and weekly paclitaxel-, gemcitabine-and doxorubicin-based regimens deserve consideration (11,14), while bevacizumab, sorafenib and pazopanib are potential target drugs (10,15,16). However, angiosarcomas are heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…The only prospective phase II study of taxane for advanced disease demonstrated responses in 5/30 (17%), though two were deemed a pathological complete response [103]. A retrospective analysis comparing the response of metastatic angiosarcoma to doxorubicin with the response to weekly paclitaxel suggested similar efficacy [104].…”
Section: Advanced Diseasementioning
confidence: 99%
“…Angiosarcoma response to paclitaxel has not been directly compared with doxorubicin in clinical trials, but a retrospective analysis suggested similar overall response rates [104]. There has been particular interest in paclitaxel as a chemotherapy option for the treatment of angiosarcoma.…”
Section: Drug Studiesmentioning
confidence: 99%